Recycle Ground Water Treatment Plant Sludge for Advanced Oxidation Process to treat Batik Wastewater - Binti Ahmad Nazari, Nadia Athirah (Universiti Teknologi PETRONAS, 2018)

(untitled)
Homemade textile industry is very famous in the East Coast of Peninsular Malaysia, which is throughout Kelantan and Terengganu. Known locally as Batik Industries, they are traditionally inherited from generation to generation. Batik Industries makes a big contribution to the economic growth due to high demands locally and from abroad. However, this industry produces wastewater which contributes to water pollution since it utilizes a lot of chemicals. Because the presence of various chemicals in the effluents, Advanced Oxidation Processes (AOP) have been selected in order to remove the Colour and COD. The Fenton method was applied to the removal of chemical oxygen demand (COD) and colour from batik wastewater industry in which the optimum pH is 9.